Insulin-Like Growth Factor and Epidermal Growth Factor Signaling in Breast Cancer Cell Growth: Focus on Endocrine Resistant Disease - Kallirroi Voudouri; Aikaterini Berdiaki; Maria Tzardi; George N. Tzanakakis; Dragana Nikitovic (Analytical Cellular Pathology)
Breast cancer is the most common type of cancer for women worldwide with a lifetime risk amounting to a staggering total of 10%. It is well established that the endogenous synthesis of insulin-like growth factor (IGF) and epidermal growth factor (EGF) polypeptide growth factors are closely correlated to malignant transformation and all the steps of the breast cancer metastatic cascade. Numerous studies have demonstrated that both estrogens and growth factors stimulate the proliferation of steroid-dependent tumor cells, and that the interaction between these signaling pathways occurs at several levels. Importantly, the majority of breast cancer cases are estrogen receptor- (ER-) positive which have a more favorable prognosis and pattern of recurrence with endocrine therapy being the backbone of treatment. Unfortunately, the majority of patients progress to endocrine therapy resistant disease (acquired resistance) whereas a proportion of patients may fail to respond to initial therapy (de novo resistance). The IGF-I and EGF downstream signaling pathways are closely involved in the process of progression to therapy resistant disease. Modifications in the bioavailability of these growth factors contribute critically to disease progression. In the present review therefore, we will discuss in depth how IGF and EGF signaling participate in breast cancer pathogenesis and progression to endocrine resistant disease.